Technical planning parameters for the development of future car models with reference to the optimal works structure for the manufacture of car bodies - Rutherford, Oliver Stuart (2006)
Abstract The digital factory is a broad computer based concept, which overwhelmingly integrates realworld facilities into high-level information systems. The objective is to represent key characteristics of the entire operational base on a common computer platform. The main pillar of this 'new' concept is simulation modelling, which allows planners to reproduce reality through easy to use computer software. Simulation attempts to reveal how existing or ideal systems work or should work and is increasingly applied in managerial decision making. This 'new' planning concept draws upon on two equally important inputs for its models: 1. process knowledge 2. technical planning parameters. Operations expertise in the form of process knowledge and planning parameters, such as cycle time or availability, directly affect the outcomes of simulation modelling. Accuracy of both factors is indispensable for making simulation models as realistic as possible. But this is challenging to accomplish! The difficulty to acquire profound process knowledge, which often takes years of experience, is frequently ignored by advocates of the digital factory. Likewise, little attention is paid to the challenge of retrieving and processing accurate planning parameters to feed into simulation models. Accuracy [or rather inaccuracy] is a latent obstacle for simulation and the digital factory as a whole. Research and industry need to be aware of potential impacts. Only the correct identification of possible shortfalls will make digital planning a precise and trusted tool for management and research in the years to come.